Implementasi Metode Focus Group Discussion (FGD) Pada Pembelajaran Bahasa Arab di Institut Nahdlatul Ulama Ciamis - Holis, Holis; Fitriani, Laily; Aziz, Abdul (Borneo Journal of Language and Education, 2024)
The importance of FGD (Focus Group Discussion) in Arabic language learning cannot be underestimated. Without FGDs, communication skills and Arabic vocabulary acquisition will stagnate. FGD is not just a method, but a vital bridge that connects students with a deep understanding of culture, context, and linguistic nuances that cannot be achieved through conventional methods. Therefore, this study aims to examine and apply the Focus Group Discussion method to Arabic language learning in the Islamic Counseling Guidance Study Program of Institut Nahdlatul Ulama (INU) Ciamis and identify the challenges and successes in applying the FGD method to Arabic language learning. The research method used involves qualitative analysis of data from classroom observations and document analysis. The data analysis technique used in this research is the Miles and Huberman data analysis model, namely data reduction, data presentation and conclusion drawing. The results of the study explain the implementation of the Focus Group Discussion method comprehensively from the opening of the FGD to the closing. The challenge found in the implementation of the FGD method is the limited time that is already tight according to the lecture schedule. The success is the active participation of students in equalizing perceptions together with a deeper understanding.